AIRLINE COMPANIES ECONOMIC SAFETY FUNDAMENTAL PRINCIPLES WITHIN THE SYSTEM OF NATIONAL SAFETY - Bezzubov, Dmitry (Proceedings of National Aviation University (archive), 2017)
Purpose: an analysis of existing threats, dangers and challenges to aviation enterprises in today's conditions and formulating the basic foundations for the development of methods for ensuring the economic security of aviation enterprises. Determination of the place and role of economic security of aviation enterprises in the national security system. Research methods: Using the comparative method of scientific knowledge, the main threats in the activity of aviation enterprises have been identified and the main provisions for increasing the level of economic stability and transport safety of aviation enterprises have been identified through the use of a formal legal and imperative method. Results: The problem of economic security of aviation enterprises is determined through the teaching of administrative, air, space law and the application of the findings of the science of economics and management. Each of the sciences forms an interdisciplinary approach to the issue of economic security of aviation enterprises in the national security system. In the modern economic system, the problem of the economic security of aviation enterprises is formed through the prism of the state's activities and the possibilities for interference in the activities of economic entities in the aviation sphere. The definition of economic security of aviation enterprises in the national security system is determined through the presence of the following economic and legal factors: a) increasing the level of protection of passengers and pilots from acts of unlawful interference; B) the formation of quality of aircraft servicing as an element of reducing the risk of accidents in aviation transport; c) the mathematical increase in the number of incidents in aviation transport; c) the integral relationship between the economic performance of the airline company and the quality of passenger service; d) the need and possibility of using air transport for humanitarian missions; Military objectives; F) the formation of a system of national security in the face of new challenges and threats to national interests; E) the need for an integrated approach to aviation security and others. Discussion: In this article, the author proposes the main provisions for increasing the level of economic security of aviation enterprises.